PENGARUH KOMITMEN PROFESIONAL, KELEBIHAN BEBAN KERJA, KONFLIK PERAN DAN LOCUS OF CONTROL PADA KEPUASAN KERJA AKUNTAN PENDIDIK - Trisna Aryani, Komang (E-Jurnal Akuntansi, 2015)
The aim of researchers to test the accountant educators ’s job satisfaction measured through professional commitment, work overload, role conflict and Locus of Control (LOC). Job satisfaction is an affective state that describes the feelings of employees on the job. Job satisfaction is a difference of something that should have been there with something that actually exists. This study was conducted on a number of accounting faculty accountant degree in the Faculty of Economics and Business, University of Udayana. The number of respondents who researched many as 39 people. Methods of sampling using purposive sampling that the sample is determined based on certain criteria. Data collected through questionnaires. With multiple linear regression analysis obtained educators accountant job satisfaction positively influenced by professional commitments while  work overload, role conflict and locus of control respectively have no effect on job satisfaction accountant educators .
Keywords: job satisfaction, professional commitment, accountant educators